2017
DOI: 10.15252/embr.201743947
|View full text |Cite
|
Sign up to set email alerts
|

Murine cytomegalovirus IE3‐dependent transcription is required for DAI/ZBP1‐mediated necroptosis

Abstract: DNA-dependent activator of interferon regulatory factors/Z-DNA binding protein 1 (DAI/ZBP1) is a crucial sensor of necroptotic cell death induced by murine cytomegalovirus (MCMV) in its natural host. Here, we show that viral capsid transport to the nucleus and subsequent viral IE3-dependent early transcription are required for necroptosis. Necroptosis induction does not depend on input virion DNA or newly synthesized viral DNA A putative RNA-binding domain of DAI/ZBP1, Zα2, is required to sense virus and trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
60
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 66 publications
6
60
0
1
Order By: Relevance
“…In two recent articles published in EMBO Reports and The EMBO Journal (Maelfait et al , ; Sridharan et al , ), the authors investigated the mechanism of ZBP1‐mediated activation of necroptosis by MCMV infection (Fig ). Since the WT virus efficiently blocks this mechanism by the expression of M45, they studied a previously characterized MCMV expressing a mutated form of M45 (MCMV‐M45 mutRHIM ) that fails to inhibit necroptosis.…”
Section: Model For Zbp1‐mediated Activation Of Necroptosis By Recognimentioning
confidence: 99%
See 4 more Smart Citations
“…In two recent articles published in EMBO Reports and The EMBO Journal (Maelfait et al , ; Sridharan et al , ), the authors investigated the mechanism of ZBP1‐mediated activation of necroptosis by MCMV infection (Fig ). Since the WT virus efficiently blocks this mechanism by the expression of M45, they studied a previously characterized MCMV expressing a mutated form of M45 (MCMV‐M45 mutRHIM ) that fails to inhibit necroptosis.…”
Section: Model For Zbp1‐mediated Activation Of Necroptosis By Recognimentioning
confidence: 99%
“…Since the WT virus efficiently blocks this mechanism by the expression of M45, they studied a previously characterized MCMV expressing a mutated form of M45 (MCMV‐M45 mutRHIM ) that fails to inhibit necroptosis. By mutating or deleting ZBP1 ZBDs, the authors uncovered a crucial role of nucleic acid binding function of ZBP1 in MCMV‐M45 mutRHIM ‐induced necroptosis (Maelfait et al , ; Sridharan et al , ). Sridharan et al () reported that although deletion of Zα1 and Zα2 ZBP1 ZBDs decreased cell death induced by MCMV‐M45 mutRHIM , point mutations in these domains of residues critical for ZBP1 interaction with nucleic acids delayed cell death but did not significantly inhibit it.…”
Section: Model For Zbp1‐mediated Activation Of Necroptosis By Recognimentioning
confidence: 99%
See 3 more Smart Citations